1999
DOI: 10.1111/j.1151-2916.1999.tb02082.x
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Synthesis of Aluminum Nitride Particles and Whiskers

Abstract: Aluminum nitride (AlN) was produced via the combustion synthesis of loosely packed aluminum powder (pore fraction of ∼0.8) in a graphite reactor that was lined with permeable carbon felt. Almost-complete conversion was achieved with a forced flow of nitrogen for beds 50-150 mm deep (mass of 200-650 g). The product was in the form of a loosely aggregated bed, with regions of distinct morphology, and had a predominantly whisker morphology. Some control over the microstructure was possible by changing the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 24 publications
0
38
1
1
Order By: Relevance
“…The high velocity of surface acoustic waves (SAW) in AlN makes it a versatile material for various SAW devices, especially SAW receivers for harsh environments [24]. AlN is also expected to be an excellent reinforcement in composites for functional or structural performance [25], such as a filler for a synthetic resin or rubber admixture [26].…”
Section: Introductionmentioning
confidence: 99%
“…The high velocity of surface acoustic waves (SAW) in AlN makes it a versatile material for various SAW devices, especially SAW receivers for harsh environments [24]. AlN is also expected to be an excellent reinforcement in composites for functional or structural performance [25], such as a filler for a synthetic resin or rubber admixture [26].…”
Section: Introductionmentioning
confidence: 99%
“…[8] Aluminum nitride (AlN), one of the important III-nitride wide band-gap (6.2 eV) semiconductors, possesses outstanding thermal conductivity, a low coefficient of thermal expansion which closely matches that of silicon, excellent mechanical strength, and chemical stability. [9] All these properties make AlN an excellent candidate for electrical insulation applications such as microelectronics packages, power transistors, and heat sinks, as well as for field emission device applications, because they exhibit a very small and even negative electron affinity, meaning that electrons excited into the conduction band can be easily emitted to vacuum level. [9][10][11] In the meantime, several papers have reported that the surface of AlN and binary AlN thin films have displayed positive electron affinity, because of the contamination by oxygen in the surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[9] All these properties make AlN an excellent candidate for electrical insulation applications such as microelectronics packages, power transistors, and heat sinks, as well as for field emission device applications, because they exhibit a very small and even negative electron affinity, meaning that electrons excited into the conduction band can be easily emitted to vacuum level. [9][10][11] In the meantime, several papers have reported that the surface of AlN and binary AlN thin films have displayed positive electron affinity, because of the contamination by oxygen in the surfaces. [12,13] Accordingly, it is significant that the oxygen in the surface of AlN materials should be removed in order that they be worthy field emission candidates.…”
Section: Introductionmentioning
confidence: 99%
“…This method is advantageous because the reaction times are short, the equipment required is simple, and the products are of high purity. However, the combustion synthesis of AlN under nitrogen pressure usually requires a large amount of AlN to be added as a diluent to lower the combustion temperatures [8][9][10][11]. Besides, to improve the nitridation conversion rate, ammonium halides such as NH 4 Cl or NH 4 F have been added to the raw materials.…”
Section: Introductionmentioning
confidence: 99%